Does business cycle have an impact on entrants and exits? - Nikolay Sterev; Diana Kopeva; Dimitar Blagoev (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: The role of entrants and exits has enlarged indisputably over recent years. The basic explanation is connected to the deepening of innovation's influence on industrial growth. Furthermore, new businesses have to be more effective, and based on products, technological or organizational innovations, and exits have to be ineffective (respectively unprofitable), based on denoted products or technology. Design/methodology/approach: According to the above-mentioned prerequisites, policymakers need to manage the role (respectively the impact) that entrants (new start-up companies) and exits play in industrial growth. Nevertheless, this impact is not a cornerstone of the Bulgarian National Strategy, or the Europe 2020 Strategy. Findings: The paper tries to answer the following two questions: 1) Do new start-up companies and exits have any role and influence on economic growth in Bulgaria?, and 2) Does the role (respectively the impact) of entrants and exits in industrial growth change according to economic cycle? Research limitations/implications: In addition, according to the Lisbon Strategy, as well as the European Union's (EU) Strategy 2020, the current economic policy supports entrepreneurship and innovations. Thus, the establishment of innovative companies, as well as the development of innovative, incumbent business are core issues of EU economic policy for the past decade. Originality/value: The paper builds on the industrial dynamic methodology and on the understanding of how business decisions (entrepreneurship, innovations, and R&D) on micro level correspond to macro level (GDP growth and innovation policy).
Keywords: O47; M13; 330; Start-up companies; entrants; exits; economic growth; Bulgaria